Konsep Modernisasi dan Reformasi Pemikiran Islam Dalam Bidang Kalam - Sigit Adi Pratomo (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This paper discusses the concept of modernization and reform of Islamic thought in the field of kalam. The development of the history of Islamic culture and thought consists of three periods: the classical period which lasted from 650-1250 AD, the medieval period which lasted from 1250-1800 AD, the modern period which lasted from 1800 AD until now. Then came many figures who called for ideas as well as reform movements that contained the vision of Islamic civilization. In the field of kalam, their thoughts have varied patterns, according to the circumstances and conditions of the people. In an advanced society, the thinking of kalam tends to be rational, which requires that everything is logical and empirical. In developing societies, most likely on the midline. Meanwhile, in disadvantaged communities, the thinking of kalam will tend to lead to the concept of jabariyah which surrenders to everything that is in front of it. Several prominent Islamic thinkers in the field of kalam in modern times include Muhammad Abduh, Sayyid Ahmad Khan Ismail Raji Al-Faruqi, Hasan Hanafi and so on. Each of them shows a different pattern in understanding religious texts which then gives birth to their own understanding of kalam. From this, a question arises from the author, how is the concept of modernization and reform of Islamic thinkers as mentioned above in the field of kalam. The conclusion in this paper uses a historical approach, with the aim of trying to reveal the values of truth in society so that it should be actualized in the future. Keywords: Modernization, Reform, Islamic Thought, Kalam